Aid and child health: Local effects of aid on stunting in Malawi - Dick Durevall; Ann-Sofie Isaksson (Research Institute of Industrial Economics (IFN), 2022)
Motivated by a recent setback in the fight against child malnutrition, this study explores whether aid projects help to reduce stunting, or impaired growth, among children in the local area. Focusing on Malawi, a country with very high stunting prevalence and for which we have access to geo-referenced data on aid projects from a broad range of donors, we geographically match spatial data on 778 aid project sites of 22 different donors with anthropometric and background data on 26,604 children under the age of 5. To identify the effect of aid, we rely on spatial and temporal variation in aid project coverage and survey rollout, coupled with variation in childbirth years in relation to project start. The empirical results consistently indicate a positive impact of early life aid exposure on child growth. The positive treatment effect materializes already for children born in the early project implementation phase and lasts for children born up to 3 years after project start and is seemingly driven primarily by multilateral aid and projects focusing on rural development, vulnerability, infrastructure, and education.
Keywords: F35; I15; O12; O15; 330; Aid; stunting; malnutrition; child health; Malawi; Africa